Impact of first-line antiretroviral therapy regimens on the restoration of the CD4/CD8 ratio in the CNICS cohort. (24th March 2020) - Herrera, Sabina; Fernandez-Felix, Borja M; Hunt, Peter W; Deeks, Steven G; Sainz, Talía; Heath, Sonya L; Achenbach, Chad J; Rodríguez, Benigno; Mathews, Christopher; Christopoulos, Katerina; Mayer, Kenneth; Napravnik, Sonia; et al.
Abstract: Background: The CD4/CD8 ratio is an indicator of immunosenescence and a predictor of all-cause mortality in HIV-infected patients. The effects of different ART regimens on CD4/CD8 ratio recovery remain unclear. Methods: Clinical cohort study of ART-treated patients from the CFAR Network of Integrated Clinical Systems (CNICS). We included ART-naive adults with HIV infection who achieved undetectable HIV RNA during the first 48 weeks of treatment and had additional follow-up 48 weeks after virological suppression (VS). Primary endpoints included increase in CD4/CD8 ratio at both timepoints and secondary endpoints were CD4/CD8 ratio recovery at cut-offs of ≥0.5 or ≥1.0. Results: Of 3971 subjects who met the study criteria, 1876 started ART with an NNRTI, 1804 with a PI and 291 with an integrase strand transfer inhibitor (INSTI). After adjusting for age, sex, race, year of entry, risk group, HCV serostatus, baseline viral load and baseline CD4/CD8 ratio, subjects on an NNRTI showed a significantly greater CD4/CD8 ratio gain compared with those on a PI, either 48 weeks after ART initiation or after 48 weeks of HIV RNA VS. The greater CD4/CD8 ratio improvement in the NNRTI arm was driven by a higher decline in CD8 counts. The INSTI group showed increased rates of CD4/CD8 ratio normalization at the ≥1.0 cut-off compared with the PI group. Conclusions: NNRTI therapy was associated with a greater increase in the CD4/CD8 ratio compared with PIs. NNRTI- and INSTI-based first-line ART were associated with higher rates of CD4/CD8 ratio normalization at a cut-off of 1.0 than a PI-based regimen, which might have clinical implications.